Activation of HIF-1α does not increase intestinal tumorigenesis - Xue, Xiang (American Physiological Society, 2014)
The hypoxic response is mediated by two transcription factors, hypoxia-inducible factor (HIF)-1α and HIF-2α. These highly homologous transcription factors are induced in hypoxic foci and regulate cell metabolism, angiogenesis, cell proliferation, and cell survival. HIF-1α and HIF-2α are activated early in cancer progression and are important in several aspects of tumor biology. HIF-1α and HIF-2α have overlapping and distinct functions. In the intestine, activation of HIF-2α increases inflammation and colon carcinogenesis in mouse models. Interestingly, in ischemic and inflammatory diseases of the intestine, activation of HIF-1α is beneficial and can reduce intestinal inflammation. HIF-1α is a critical transcription factor regulating epithelial barrier function following inflammation. The beneficial value of pharmacological agents that chronically activate HIF-1α is decreased due to the tumorigenic potential of HIFs. The present study tested the hypothesis that chronic activation of HIF-1α may enhance colon tumorigenesis. Two models of colon cancer were assessed, a sporadic and a colitis-associated colon cancer model. Activation of HIF-1α in intestinal epithelial cells does not increase carcinogenesis or progression of colon cancer. Together, the data provide proof of principle that pharmacological activation of HIF-1α could be a safe therapeutic strategy for inflammatory bowel disease.